Continuous care needs in patients with cancer receiving chemotherapy during the recent omicron wave of COVID-19 in Shanghai: A qualitative study - Zhang, Jie; Wang, Caifeng; Huang, Lei; Zhang, Jun (Frontiers in Psychology, 2023)
Aims: This study aimed to investigate the care needs, to clarify the factors affecting the quality of home-care, and to provide reference for constructing a home-care system for patients with cancer receiving chemotherapy during the recent omicron wave of COVID-19 in Shanghai. Methods: From March to May 2022 when the omicron wave emerged in Shanghai, 50 consecutive patients who received chemotherapy at Ruijin Hospital, Shanghai Jiao Tong University School of Medicine were enrolled, and underwent face-to-face or telephone-based semi-structured interviews regarding continuous care needs. Some of their homecare-givers, caring nurses and physicians were also interviewed. The Colaizzi method was used for data analysis. Results: Fifty patients, 4 homecare-givers, 4 nurses, and 4 physicians were interviewed. Three themes and six subthemes emerged from analysis of the interviews: The first theme was “Disease management needs”, including needs for knowledge of managing adverse events associated with chemotherapy, and needs for treatment-related information. Patients expressed most concern about not being able to go to the hospital for blood review and disease evaluation in time due to the outbreak. With the COVID-19 pandemic being ongoing, factors such as pandemic panic, inconvenient medical treatment, and worry about hospital cross-infection might reduce disease management for patients with cancer. The second theme was “Medical needs”, including needs for mobile healthcare and needs for medical resources. All interviewees emphasized the importance of mobile healthcare during the COVID-19 pandemic, as access to hospitals was difficult. The third theme was “Spiritual needs”, including demands for psychological counseling and intervention, and needs for spiritual care. Patients and homecare-givers commonly lacked a feeling of security and needed communication, encouragement, and reassurance that medical care could be delivered to them, and patients reported that they very much wanted psychological advice. Conclusions: For patients with cancer receiving chemotherapy during the COVID-19 pandemic, continuous care are greatly needed. Medical personnel should strengthen the healthcare education for patients and their caregivers during hospitalization, and further improve the patients’ information intake rate through Internet-based digital healthcare methods during home-care, to further meet the information needs of patients after discharge from hospital.